The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.13189/bb.2021.080201
|View full text |Cite
|
Sign up to set email alerts
|

Biotreatment of Effluent from Cassava Processing Using Powdered Seeds of Moringa oleifera

Abstract: The world is facing increasingly more severe water security issues. It has, therefore, become imperative to develop sustainable, eco-friendly water management and recycling techniques. This study assessed the capacity of powdered seeds of Moringa oleifera to improve water quality of effluent from two (2) cassava processing plants in Umudike, Nigeria by measuring the variations in specific physicochemical and microbiological parameters of the samples. The biodegradability indices of the wastewater samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…40 Num. 1: 19-28 (June 2023) was used for evaluating the potential cassava mill effluent treatment (Ibiene et al, 2021).…”
Section: Description Of the Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…40 Num. 1: 19-28 (June 2023) was used for evaluating the potential cassava mill effluent treatment (Ibiene et al, 2021).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The physicochemical parameters that were assessed in the present study includes turbidity, total organic carbon (TOC), biochemical oxygen demand (BOD), chemical oxygen demand (COD), pH, and temperature (APHA, 2011;Ibiene et al, 2021). BOD: CME sample was collected and divided into two portions.…”
Section: Determination Of Physicochemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers focused on cassava wastewater treatment through several strategies, such as phytoremediation/bioremediation, electrocoagulation, anaerobic treatment, activated sludge, and coagulation (de Faria Ferreira Carraro et al, 2021;Fleck et al, 2017;Ibiene et al, 2021;Kaewkannetra et al, 2011;Nuraini and Felani, 2015;Paulo et al, 2013;Sudibyo et al, 2017). Coagulation is chosen as the more effective technique due to its efficiency, economic, and facile operation, and it also shows satisfying results (Aguilar et al, 2003;Ahmad et al, 2005;Adebowale et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Trevisan et al (2019) started to observe the coagulation ability of Moringa oleifera seeds extract and reported the removal of turbidity at 89.16% and COD at 66.39% from the cassava wastewater. Ibiene et al (2021) reported that coagulants from Moringa oleifera powdered seeds successfully reduced the COD by up to 74.1% and turbidity by up to 63.2% from the cassava wastewater. Differently, dos Santos et al ( 2018) applied different commercial coagulants (Acquapol WW, Acquapol S5T, Tanfloc SL, and Tanfloc SG) to observe the effectivity on cassava wastewater removal.…”
Section: Introductionmentioning
confidence: 99%